KETERKAITAN ANTARA STIGMA, KEYAKINAN, DAN NIAT KELUARGA DALAM MENeARI PERTOLONGAN UNTUK ANGGOTA KELUARGA YANG RENTAN MENGALAMI GANGGUAN MENTAL DI YOGYAKARTA - Salim, Azlizamani bin Zubir Salim (2014)
The study aimed to analyze the influence of belief causes of mental disorders on seeking help intention with attitude as intervening variable, influence of belief norm on seeking help intention with subjective norm as intervening variable, and the influence of control belief on seeking help intention with control behavior as intervening variable for family with mental disorder in Yogyakarta. The analysis used path analysis data processing by SmartPLS 3.0. The finding of the research showed that there are significant causes of mental illness beliefs through the intervening variable-seeking attitudes, normative beliefs influence through an intervening variable subjective norm, and control beliefs influence through an intervening variable control on the intention-seeking behavior. The belief causes of mental disorders, the influence of normative beliefs, and beliefs influence the control has no direct influence on the intention-seeking scholars. There are differences in the intention to search for help when using the help of a psychiatrist, scholars, and shaman. Intention to search for help did not differ between rural and urban communities. Keywords: mental disorder, stigma, belief causes of mental disorders, control beliefs, subjective norm, attitudes toward seeking help, behavioral control, seeking help intention